Effect of phase advance on the brushless dc motor torque speed respond - Mohd, M.S. (Institute of Physics Publishing, 2015)
Brushless direct current (BLDC) motor is widely used in small and medium sized electric vehicles as it exhibit highest specific power and thermal efficiency as compared to the induction motor. Permanent magnets BLDC rotor create a constant magnetic flux, which limit the motor top speed. As the back electromotive force (EMF) voltage increases proportionally with motor rotational speed and it approaches the amplitude of the input voltage, the phase current amplitude will reach zero. By advancing the phase current, it is possible to extend the maximum speed of the BLDC motor beyond the rated top speed. This will allow smaller BLDC motor to be used in small electric vehicles (EV) and in larger applications will allow the use of BLDC motor without the use of multispeed transmission unit for high speed operation. However, increasing the speed of BLDC will affect the torque speed response. The torque output will decrease as speed increases. Adjusting the phase angle will affect the speed of the motor as each coil is energized earlier than the corresponding rise in the back emf of the coil. This paper discusses the phase advance strategy of Brushless DC motor by phase angle manipulation approaches using external hall sensors. Tests have been performed at different phase advance angles in advance and retard positions for different voltage levels applied. The objective is to create the external hall sensor system to commutate the BLDC motor, to establish the phase advance of the BLDC by varying the phase angle through external hall sensor manipulation, observe the respond of the motor while applying the phase advance by hall sensor adjustment.